2009
DOI: 10.1002/jmri.21871
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of mediastinal tumors with diffusion‐weighted single‐shot echo‐planar MRI

Abstract: Purpose:To assess the role of diffusion-weighted singleshot echo-planar magnetic resonance imaging (MRI) in patients with mediastinal tumors. Methods:Prospective study was conducted on 45 consecutive patients (29 male, 16 female, age 22-66 years, mean 41 years) with mediastinal tumor. They underwent diffusion-weighted single-shot echo-planar MRI of the mediastinum with a b-factor of 0, 300, and 600 sec/mm 2 . The apparent diffusion coefficient (ADC) value of the mediastinal tumor was correlated with the histop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 36 publications
(36 reference statements)
5
56
6
1
Order By: Relevance
“…13,[25][26][27][28] In contrast with Abdel Razek, that distinguished Masaoka-Koga stage I disease (non-invasive THY) from higher stages (II-IV, invasive THY), we assessed whether DW-MRI could distinguish stage I-II (non-advanced THY, no neo-adjuvant therapy before surgery required), from stage III-IV (advanced THY, neo-adjuvant treatments needed). 11 Although we found a significantly higher mean ADC in non-advanced THY compared to advanced THY, this finding may have been influenced by the higher percentage of type B3 THY in advanced THY subgroup (56% versus 7% of nonadvanced THY subgroup). Indeed, the lower ADC values generally found in malignant tumors compared to benign conditions are related to a combination of higher cell density, tissue disorganization, and increased extracellular space tortuosity, all contributing to reduced motion of water.…”
Section: Discussioncontrasting
confidence: 68%
See 3 more Smart Citations
“…13,[25][26][27][28] In contrast with Abdel Razek, that distinguished Masaoka-Koga stage I disease (non-invasive THY) from higher stages (II-IV, invasive THY), we assessed whether DW-MRI could distinguish stage I-II (non-advanced THY, no neo-adjuvant therapy before surgery required), from stage III-IV (advanced THY, neo-adjuvant treatments needed). 11 Although we found a significantly higher mean ADC in non-advanced THY compared to advanced THY, this finding may have been influenced by the higher percentage of type B3 THY in advanced THY subgroup (56% versus 7% of nonadvanced THY subgroup). Indeed, the lower ADC values generally found in malignant tumors compared to benign conditions are related to a combination of higher cell density, tissue disorganization, and increased extracellular space tortuosity, all contributing to reduced motion of water.…”
Section: Discussioncontrasting
confidence: 68%
“…8 reported for non-invasive THY in previous studies. 10,11 This discordance could be related to the "perfusion bias" with a consequent overestimation in ADC measurements of those studies. Indeed, as both the investigators used also the images obtained with b values of 0 s/mm 2 for the ADC computation, the ADC value was determined not only by diffusion (related to cell density and cellular architecture) but also by tissue perfusion.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…T 2 weighted MRI was superior to pre-contrastenhanced CT in the depiction of the internal heterogeneity of the tumour. Razek et al 15 and Gumustas et al 16 reported that the mean apparent diffusion coefficient (ADC) of malignant mediastinal masses was significantly lower than that of benign mediastinal masses. They also mentioned that cystic or necrotic parts interfered with ADC value.…”
Section: Discussionmentioning
confidence: 99%